Inheritance after Apocalypse: the Dystopian Environment (Altre Modernità, 2013)
Utopias are perfect places but the term itself says that they are nowhere to be found, making them practically impossible. Dystopias, even if they are written as a warning of how things can get worse, seem much more probable. All utopian societies are systems of plenty where everyone has enough and no one lacks the basic necessities. Yet resources do not come out of nowhere. A political system may be needed in a utopia but it is not the sole condition. A barren environment would make perfection impossible. A devastated land, then, can lead to a dystopia. Our way of life is connected to the environment around us. A drastic change there would alter human behavior significantly. If utopia is the dream situation, the dystopia is obviously the nightmare. The late 20th century had a feeling of “the end”, a lot of finalities were imagined, including “the end of history”. However, once those notions were left behind, even dystopias started to imagine events happening in a post-apocalyptic situation. One such dystopia is The Road, a novel about the struggles of a father and a son trying to survive after an unnamed cataclysm. The father’s desire to take his child toward the sea, where he thinks it might be safe, also implies a journey through the devastated land. In their travel they will witness the devastation of nature and the changes that brings to human behavior, a change that was unwanted and, for the son, an inheritance the father was unwilling to pass on.